TYPES OF SPEECH ACT PRESENTED BY MALE MAIN CHARACTER IN JANE AUSTEN’S NOVEL - Suryanovika, Citra (Jurnal Ilmiah Spectral, 2016)
The study focusing on the types of speech act presented by male main characters in Jane Austen’s Novel is a part of research roadmap plan. The research is aimed to find out types of speech acts presented by Edward Ferrars in the novel Sense and Sensibility. In conducting the research, the researcher used semantic and pragmatic approach to analyse types of speech acts. The research used descriptive qualitative approach to collect, analyse and present the data. The researcher conducted the research chronologically by identifying, classifying and analysing the utterances made by Edward Ferrars in Jane Austen’s novel Sense and Sensibility. The researcher identified the utterances presented by the male main character by interpreting the utterances. The researcher used Qadir and Riloff’s lexical and syntactic features that has been modified, as well as Searle Keywords focusing on four speech acts (Expressive, Representative, Directive and Commissive) to classify and analyse the utterances. The findings showed that representative speech acts are 62.6 %, followed by 20.8% directive speech acts, 8.3 % for each expressive and commissive speech acts. The identification of speech acts determine the character of Edward Ferrars, as a straightforward and curious gentleman.